Content Validity of Student Perception Instrument on School Educational Management - Helmiyatun; Taqiudin , Muhamad; Ahmad (Journal of Practice Learning and Educational Development, 2025)
This study aims to evaluate the content validity of an instrument developed to measure students' perceptions of educational management in upper secondary schools (SMA). Given the crucial role of school management in shaping students' learning experiences and academic achievement, a valid instrument is essential for comprehensively assessing students' perceptions. This study employs a quantitative approach using content validity analysis with Aiken’s V index. The validation process involves four experts in educational management as raters. The findings indicate that most instrument items exhibit moderate to high content validity, with Aiken’s V values ranging from 0.50 to 1.00. These results suggest that the developed instrument is suitable for assessing students' perceptions of school management effectiveness. However, some items require refinement to enhance clarity and alignment with the measured concept. This study provides a significant contribution to educational evaluation by offering an instrument that can serve as a reference for policymakers and educators in improving school management effectiveness. Further studies are recommended to examine construct and criterion validity and assess the instrument's reliability to ensure its applicability in various educational contexts.